Applications, drawbacks, and future scope of nanoparticle-based polymer composites - Biswas M.C.; Chowdhury A.; Hossain M.M.; Hossain M.K.
Over the earlier decades, an explosive growth of nanotechnology and nanoparticle synthesis techniques has been witnessed. The infusion of nanoparticles into polymer matrices to fabricate nanoparticle-based polymer composites has been carried out along with the advancement of nanotechnology. Unlike conventional materials, polymer nanocomposites exhibit superior performance because of the outstanding properties of nanoparticles such as high aspect ratio, unique structural attributes, and properties. This chapter focuses on recent state-of-the-art polymer nanocomposite applications that include but are not limited to food packaging, biomedical, drug delivery, sensing, energy storage, flame retardancy, microelectronics, surface coating, pollution remediation, e-textiles, etc. Lastly, the challenges and prospects of nanoparticle-based polymer composites and their potential prospective applications have also been discussed. © 2022 Elsevier Ltd. All rights reserved.
Keywords: 3D PRINTING; BIOMEDICAL APPLICATIONS; E-TEXTILES; ENERGY STORAGE; FOOD PACKAGING; NANOPARTICLES; POLLUTION REMEDIATION; POLYMER NANOCOMPOSITES